Nest-site selection and nesting success of Little Owls (Athene noctua) in Mediterranean woodland and open habitats - Tome, R; Bloise, C; Korpimaki, E (JOURNAL OF RAPTOR RESEARCH, 2004)
We studied nest-site selection by Little Owls (Athene noctua) in two Mediterranean habitats, a holm oak (Quercus rotundifolia) woodland (36 nests during 1997-99) and a steppe-like area (37 nests during 1997-99), in Southern Portugal, by comparing macrohabitat and microhabitat characteristics of used nests to those of randomly-selected nest sites. In the woodland area, predator presence seemed to be the main factor that influenced nest-site selection by owls. In the steppe area, a large number of alternative cavities around a nest appeared as the most important variable associated with nest-site selection. At this site, size of stones in stone piles also seemed to influence nest-site selection; owls nested in piles with larger than average stones. We also found tree girth was positively associated with nesting Success ill the woodland area. Larger trees held more complex cavities that may have improved the ability of adults and offspring in escaping from predators. Other variables, Such as distance to human habitations and the orientation of nest-site entrance might have influenced nesting success as well. Predation risk and the internal features of nest cavities were the most likely factors affecting nest-site selection and nesting success of Little Owls in Mediterranean habitats.
Keywords: Athene noctua; habitat selection; Little Owl; Mediterranean Region; predation risk; reproductive success

Nest-site selection and nesting success of Little Owls (Athene noctua) in Mediterranean woodland and open habitats - Tome, R.; Bloise, C.; Korpimaki, E. (JOURNAL OF RAPTOR RESEARCH, 2004)
We studied nest-site selection by Little Owls (Athene noctua) in two Mediterranean habitats, a holm oak (Quercus rotundifolia) woodland (36 nests during 1997-99) and a steppe-like area (37 nests during 1997-99), in Southern Portugal, by comparing macrohabitat and microhabitat characteristics of used nests to those of randomly-selected nest sites. In the woodland area, predator presence seemed to be the main factor that influenced nest-site selection by owls. In the steppe area, a large number of alternative cavities around a nest appeared as the most important variable associated with nest-site selection. At this site, size of stones in stone piles also seemed to influence nest-site selection; owls nested in piles with larger than average stones. We also found tree girth was positively associated with nesting Success ill the woodland area. Larger trees held more complex cavities that may have improved the ability of adults and offspring in escaping from predators. Other variables, Such as distance to human habitations and the orientation of nest-site entrance might have influenced nesting success as well. Predation risk and the internal features of nest cavities were the most likely factors affecting nest-site selection and nesting success of Little Owls in Mediterranean habitats.
The following values have no corresponding Zotero field: pub-location: 14377 117TH STREET SOUTH, HASTINGS, MN 55033 USA publisher: RAPTOR RESEARCH FOUNDATION INC
Keywords: Athene noctua; habitat selection; Little Owl; Mediterranean Region; predation risk; reproductive success